Consequences of Information and Communication Technologies and Environmental Degradation on Health Expenditure - Yuksel Bayraktar PhD; Serdar Aydin PhD; Mehmet ali Çakır PhD; Mürşit Recepoğlu PhD; Ayfer Ozyilmaz PhD; Figen Buyukakin PhD; Sümeyra Çakır PhD (SAGE Publishing, 2024)
This study aims to examine how the subcomponents and overall measurement of ecological footprint, as well as the use of information and communication technologies, affect health expenditures. For this study, the sample group consisted of the top 25 countries with the highest ecological footprint for the period 2000 to 2021. System GMM estimation results demonstrate that economic growth and ecological footprint have a positive impact on health expenditures. Covid-19 dummy variables, have a statistically significant and positive effect on health expenditures. On the other hand, information and communication technologies has a statistically significant but negative effect on health expenditures. The estimation results show that the Covid-19 pandemic increased health expenditures. Looking at the effect of subcomponents of environmental degradation on health expenditures, all subcomponents have a statistically significant and positive effect on health expenditures. It is seen that the most effective variable is forest products. The variable that has almost the same impact as the footprint of forest products is the carbon footprint. Carbon footprint has significant and positive impact on health expenditures, followed by fishing grounds cropland, grazing land, built-up land. The results of the study indicate which forms of pollution should be given priority by policymakers in order to prevent an increase in health expenditure resulting from environmental degradation.